Early surgery may lower mortality in patients suffering from severe spinal infection - Lener, Sara (Acta Neurochir (Wien), 2020)
PURPOSE: Spinal infection (SI) is a life-threatening condition and treatment remains challenging. Numerous factors influence the outcome of SI and both conservative and operative care can be applied. As SI is associated with mortality rates between 2 and 20% even in developed countries, the purpose of the present study was to investigate the occurrence and causes of death in patients suffering from SI. METHODS: A retrospective analysis was performed on 197 patients, categorized into two groups according to their outcome: D (death) and S (survival). The diagnosis was based on clinical and imaging (MRI) findings. Data collected included demographics, clinical characteristics, comorbidities, infection parameters, treatment details, outcomes, and causes of death. RESULTS: The number of deaths was significantly higher in the conservative group (n = 9/51, 18%) compared with the operative counterpart (n = 8/146, 6%; p = 0.017). Death caused by septic multiorgan failure was the major cause of fatalities (n = 10/17, 59%) followed by death due to cardiopulmonary reasons (n = 4/17, 24%). The most frequent indication for conservative treatment in patients of group D included “highest perioperative risk” (n = 5/17, 29%). CONCLUSION: We could demonstrate a significantly higher mortality rate in patients solely receiving conservative treatment. Mortality is associated with number and type of comorbidities, but also tends to be correlated with primarily acquired infection. As causes of death are predominantly associated with a septic patient state or progression of disease, our data may call for an earlier and more aggressive treatment. Nevertheless, prospective clinical trials will be mandatory to better understand the pathogenesis and course of spinal infection, and to develop high quality, evidence-based treatment recommendations.